Real-Time Change Point Detection with Application to Smart Home Time Series Data - Aminikhanghahi, Samaneh; Wang, Tinghui; Cook, Diane J. (IEEE transactions on knowledge and data engineering, 2019)
Change Point Detection (CPD) is the problem of discovering time points at which the behavior of a time series changes abruptly. In this paper, we present a novel real-time nonparametric change point detection algorithm called SEP, which uses Separation distance as a divergence measure to detect change points in high-dimensional time series. Through experiments on artificial and real-world datasets, we demonstrate the usefulness of the proposed method in comparison with existing methods.